Production of Miniature Vegetables in Florida - Donald N. Maynard (EDIS)
Revised! HS-36, a 5-page fact sheet by Donald N. Maynard, describes the culture and harvesting of specialty miniature vegetables. Includes tables of representative varieties and seed sources and harvesting and packing guidelines. Originally published by the UF Horticultural Sciences Department in January 1989, this publication has been revised and made available online September 2006.